Pengaruh Diversifikasi Portofolio Terhadap Ketahanan Keuangan Individu Di Masa Krisis Ekonomi : Studi Kasus Pada Investor Ritel Di Surabaya Selama 2019-2024 - Ayu Asari; Marcella Aullia Jayadi; Uhti Noer Choliza Safitri; Maria Yovita R.Pandin (CV. ULIL ALBAB CORP, 2024)
This study aims to analyze the effect of portfolio diversification on individual financial resilience, especially among retail investors in Surabaya, during the 2019-2024 economic crisis period. Portfolio diversification is an investment strategy used to reduce risk through asset allocation in various investment instruments. A quantitative method with a descriptive approach was used in this study, involving 50 student retail investors as samples. Data were collected through questionnaires and analyzed using simple linear regression. The results show that there is a positive and significant relationship between portfolio diversification and financial resilience, with a correlation value (R) of 0.589 and a coefficient of determination (R Square) of 34.7%. This means that portfolio diversification contributes to financial resilience by 34.7%, while the rest is influenced by other variables. The F test shows a significance value of 0.000 <0.05, which means that the alternative hypothesis is accepted, so that portfolio diversification has a significant effect on financial resilience. This research provides insight that diversification is an important strategy for retail investors to maintain their financial stability during times of crisis.